Elaboración de un manual de Buenas Prácticas de Manufactura para el proceso de faenamiento de bovinos en el Camal Municipal Riobamba - Paguay Tierra, Francisco Xavier (2019)
The Municipal Camal Riobamba is a Company managed by the GAD Riobamba and offers citizens the Service of slaughtering animal for slaughter. The purpose of this research Project is to prepare a manual of Good Manufacturing Practice for the bovine line. As a first step for the development of the manual, an initial diagnosis of the process was carried out with the support of a checklist based on the requirements shown in Resolution ARCSA-DE-067-2015-GGG, issued by the National Agency of Health Regulation, Control and Surveillance (ARCSA) in 2015.The inicial evaluation showed a low percentage of BPM compliance, due to the different drawbacks presented by sections such as facilities, operating conditions and operating personnel. Once the missing requirements were known, an manual was prepared, which contains 13 prerequisite programs (PPR) and five operational prerequisite programs (PPRO). Likewise the Hazard Analysis and Critical Control Points (HACCP) Plan, was developed, where the analysis of all the physical, chemical and biological agents detected in the process is exposed, a document that also specifies the control parameters, system of monitoring and corrective actions for the antemortem inspection, evisceration and airing stage half channels, considered as critical control Points (CCP). After the development of the documentation, an audit was carried out to verify the final situation of the process, which shows that the BPM compliance percentage increased to 74,78%. The elaboration of the prerequisite programs and the HACCP plan constitute the first step for the implementation of a Food Safety Management System, for which the Company must continue working on strategies aimed at assuring the safety of the process and product.